1993
DOI: 10.2172/10116437
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up fuel plate stability experiments and analyses for the Advanced Neutron Source

Abstract: The reactor for the plannedAdvancedNeutron Sourceuses closely spaced plates cooled by heavy water flowing through narrow channels.Two sets of tests were performedon the upperand lower fuel plates for the structuralresponseof the fuel plates to the requiredhigh coolant flow velocities. This reportcontains the data from the second round of tests. Results and conclusions from all of the tests are also included in this report. The tests were done using light wateron full-scale epoxy models, and through model theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Experimental testing of the Miller Critical Velocity has been performed by many researchers [56][57][58][59]. These experimenters found that the Miller Critical Velocity was conservative, with flows tested to with no total plate collapse.…”
Section: Overview Of Past Fuel Plate Fsi Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental testing of the Miller Critical Velocity has been performed by many researchers [56][57][58][59]. These experimenters found that the Miller Critical Velocity was conservative, with flows tested to with no total plate collapse.…”
Section: Overview Of Past Fuel Plate Fsi Analysismentioning
confidence: 99%
“…The reactor design was to meet or exceed the neutron flux characteristics of the HFIR making it the highest neutron flux reactor in the world. Due to the extremely high flow rates, extensive analysis was done to ensure the stability and integrity of the fuel plate structure in the reactor [101,63,102,103,59].…”
Section: Flow Over Curved Plate Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3)(4)(5) are expanded using Eqs. (2), three equations are realized that can be solved for the three boundary loads at @ = 0. The three boundary loads at the outside boundary can be found from equilibrium as…”
Section: -4mentioning
confidence: 99%